2001
DOI: 10.1152/ajpregu.2001.280.6.r1601
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic islet blood flow in conscious rats during hyperglycemia and hypoglycemia

Abstract: Anesthesia affects general hemodynamics and regulation of organ perfusion. We used colored microspheres to measure pancreatic islet blood flow in conscious rats at two time points, during either hyperglycemia or hypoglycemia. This method, using black and green microspheres, was validated by comparison with previous microsphere experiments and by lack of effect of a nonmetabolizable glucose analog, 3-O-methylglucose, on islet perfusion. Basal and glucose-stimulated islet blood flow levels were similar in pentob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 22 publications
1
14
3
Order By: Relevance
“…This is in contrast to previous studies, also using the microsphere technique, where either an increased [14] or an unchanged [15] islet blood flow was recorded. The reasons for the discrepancy between these studies are not known.…”
Section: Discussioncontrasting
confidence: 98%
See 3 more Smart Citations
“…This is in contrast to previous studies, also using the microsphere technique, where either an increased [14] or an unchanged [15] islet blood flow was recorded. The reasons for the discrepancy between these studies are not known.…”
Section: Discussioncontrasting
confidence: 98%
“…However, although the technique used with repeated injection of microspheres enables paired observations, it relies on the basic concept that the distribution of a second microsphere injection is not influenced by the first injection. As recently evaluated [15,35], such influence might not occur in untreated animals, although it critically depends on the embolized mass in the body. Occlusion of too many capillary beds after the first injection causes an erroneous increase in both whole pancreatic and islet blood flow as measured by a second microsphere injection [35].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…paired analysis of measurements and a reduction of the number of animals needed. In a recent study, repeated injections of differently coloured 10 m-microspheres were found to give reproducible islet blood flow measurements in awake rats (11). The present study evaluated this finding in anaesthetised rats and whether such experiments are restricted to the use of 10 m microspheres or also applicable for 15 m microspheres.…”
Section: Discussionmentioning
confidence: 80%